Original paperAlpha-bungarotoxin (α-Bgtx) and beta-bungarotoxin (β-Bgtx) binding activities in human cadaver brain - Rasool, Suhail; Jailkhani, Bansi L.; Irshad, Mohd; Behari, Madhuri; Goel, Vinay (Archives of Medical Science, 2007)
Introduction: Using 125Iα-Bgtx as a ligand, postsynaptic cholinergic nicotinic receptors has been identified in species. Presynaptic receptors can be defined as receptors at or near the nerve terminal that can positively or negatively modulate transmitter release, that directly or indirectly influence the probability of an action potential resulting in exocytosis. These receptors are identified by utilizing b-Bgtx. Our study involves the identification of these receptors in different regions of brain. Material and methods: The activity of postsynaptic AChR and presynaptic membrane receptor in membrane preparation and triton extract of muscle and brain tissue was determined by virtue of its high affinity for a and b-Bgtx by rapid filtration method in case of membrane preparations and ammonium sulphate precipitation method in triton extracts i.e; solubilized receptor. Results: Specific α-Bgtx binding as fmoles/mg tissue was observed in occipital lobe (6.1±0.1) parietal lobe (6±0.6), temporal lobe (5.2±1.4), cerebral cortex (6.2±0.3), hippocampus(5.6±0.2), hypothalamus (4.3±0.4) and brain stem (4.8±0.2). No specific binding of α-Bgtx was found in cerebellum and frontal lobe. β-Bgtx binding activity was present in all the above regions of brain and was in range of 4.2-4.9 fmoles/mg tissue. Presynaptic receptors also shows immunoreactivity with myasthenic sera. Conclusions: In addition to muscle, β-Bgtx binding proteins are present in each regions of the brain, while as a-Bgtx binding proteins are absent in some regions. β-Bgtx binding sites could play an important role in the pathogenesis of myasthenia gravis.